Optimization of Sustainability and Flood Hazard Resilience for Home Designs. (2016) - Matthews, Elizabeth; Friedland, Carol J.; Orooji, Fatemeh
Abstract: Life-cycle analysis is a beneficial tool that can be utilized to quantify the performance of buildings within the context of environmental impact metrics (e.g. carbon footprint). While typical life-cycle analysis incorporates regular building maintenance, structural repairs made as a result of natural hazard damages are largely ignored. This study presents an environmental impact design optimization model that can be used to compare multiple coastal, single-family residential (SFR) building designs subjected to coastal flood hazards based on environmental impact factors. For each design, the model measures the environment impact (i.e. embodied energy and carbon footprint) of initial construction plus flood-induced repairs. Repairs are quantified using a probability-based methodology and life-cycle analysis is used to measure environmental impacts. Design options can then be compared and optimal designs that meet performance-based resilience and sustainable design objectives can be selected. A case study is presented for an SFR building located in coastal St. Petersburg, Florida, USA, and demonstrates that up to a 64% reduction in embodied energy and carbon footprint can be achieved over a 50 year building life through more resilient component configurations and materials and by increasing first floor elevations.